Influence of the desiccant wheel effectiveness method approaches, with fix and variable effectiveness parameters, on the performance results of an airport air-conditioning system - Ruivo, Celestino Rodrigues; Fernández Hernández, Francisco; Cejudo López, José Manuel (Energy conversion and management, 2015)
[Display omitted] •Desiccant-assisted cooling system performance is simulated.•Desiccant wheel is simulated by the effectiveness method.•Approaches based on constant and variable effectiveness parameters are tested.•Predicted results with constant effectiveness parameters are questionable.•Several ranges for the regeneration temperature and airflow rates are analysed. This work focuses on the dynamic simulation of an air conditioning system of an airport located in the Mediterranean coast of Andalusia–Spain. It incorporates a desiccant dedicated outdoor air system that operates under variable air volume control strategy. This unit is coupled to a solar source thermal system and to a source heat pump. Several versions of the effectiveness method, applied to the desiccant wheel and based on variable and fix effectiveness parameters, are tested. It is clearly demonstrated that simple approaches based on constant effectiveness parameters, which have been commonly adopted by several authors, provide questionable results. A parametric study investigating the influence of imposing different ranges for the regeneration temperature (minimum of 50°C and maximum of 80°C) and for the airflow rates (maximum inlet mass velocity of 3kgs−1m−2) on the performance results of the system is conducted by considering a suitable approach based on variable effectiveness parameters. Depending on the version of the case simulated: (i) the electrical coefficient of performance of the system varies from 1.22 to 4.07 and (ii) the fraction of time period on August that the system is not able to control the humidity of the zone ranges from 0 to 0.2715. The best case providing controllability of the humidity of the zone during the whole period is characterized by a regeneration temperature range of 50–70°C and constant airflow rate (inlet mass velocity of 3kgs−1m−2). The coefficient of performance in this case is 3.2.